Ballot Casting Assurance via Voter-Initiated Poll Station Auditing - Benaloh, Josh (Proceedings of the 2007 Electronic Voting Technology Workshop, 2007)
The technology for verifiable, open-audit elections has advanced substantially since research on this topic began a quarter century ago. Many of the problems are well-understood and have solid solutions. Ballot casting assurance — the problem of ensuring that a programmatically encrypted ballot matches the intentions of an individual human voter — has recently been recognized as perhaps the last substantial obstacle to making this technology fully viable. Several clever schemes have been developed to engage humans in interactive proofs to challenge and check validity of each ballot cast, but such a high standard may be neither practical nor necessary. If done properly, substantial integrity can be obtained by giving voters and observers the option to challenge ballot validity without requiring all voters to do so. This option can be made unobtrusive so as to not interfere with the normal process for most voters, but there are numerous risks and subtleties that necessitate a careful examination of the process. This paper identifies some heretofore unobserved issues with this “simple” method of casting ballots and describes a detailed process that mitigates all known threats. In doing so, it provides a blueprint for how verifiable, open-audit elections can reasonably be conducted in practice.